Wordwall Game Method as an Effort to Improve Student Learning Outcomes at MI Ulul Azmi Makassar - Laila Bansur; Laemah (MANDAILING GLOBAL EDUKASIA, 2025)
This research seeks to examine the effectiveness of the Wordwall game method in enhancing learning outcomes on the topic of Nikmat Syukur at MI Ulul Azmi Makassar. The study employs a Classroom Action Research (CAR) approach, conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The participants consisted of 25 fifth-grade students from MI Ulul Azmi Makassar. Data were gathered through tests on learning outcomes, observations, and documentation. The findings revealed that implementing the Wordwall game method led to improved student performance. In the first cycle, the student mastery level was 65%, categorized as sufficient. After making improvements in the second cycle, the completion rate rose to 85%, classified as good. This improvement indicates that the Wordwall game not only enhances students' understanding of the material but also boosts their motivation and engagement in the learning process. As an interactive learning tool, this method contributes to a more enjoyable and engaging classroom environment. Therefore, the Wordwall game method can serve as an effective alternative for improving student learning outcomes.